Motor Impairments in Angelman Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Of 33 children and adolescents (median age 6 years) investigated for learning disability, epilepsy, and motor dysfunction to detect suspected Angelman syndrome (AS), in a study at Goteborg University, Sweden, 23 fulfilled criteria for AS.